The roles of fear of negative evaluation and social anxiety in the relationship between self-compassion and loneliness: a serial mediation model - Liu, Xinyi; Yang, Ying; Wu, Hang; Kong, Xiangjing; Cui, Lijuan (Current psychology (New Brunswick, N.J.), 2022)
Loneliness is an unpleasant experience of lacking desired interpersonal relationships. Abundant evidence has clarified the negative outcomes of loneliness, such as anxiety, even suicidal behaviors. However, relatively few is known about the internal buffering elements for loneliness, especially in adolescents. The current research aimed to investigate the relationship between self-compassion and adolescents’ loneliness, as well as the mediating roles of fear of negative evaluation and social anxiety in this relationship. A total of 871 Chinese adolescents completed a set of questionnaires, including the measures of loneliness, self-compassion, social anxiety and the fear of negative evaluation. We tested the proposed serial mediation model and the results suggested that self-compassion was negatively associated with loneliness, and social anxiety served as a mediator in the relationship. Besides, we found that the fear of negative evaluation and social anxiety serially mediated the negative association. Specifically, self-compassionate adolescents reported less fear of negative evaluation, which resulted in decreased social anxiety symptoms. In turn, the decreased social anxiety was linked to reduced feelings of loneliness. The present study sheds lights on the mediating effects of fear of negative evaluation and social anxiety in the relationship between self-compassion and loneliness. The theoretical and practical implications, as well as the limitations of the present study, are discussed.